CHARACTERISTICS OF DEVELOPMENT OF THE REGIONAL ECONOMY OF THE REPUBLIC OF UZBEKISTAN - Musurmonova M.O. (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article is dedicated to the comprehensive research of the economic growth rates of the regions of the Republic of Uzbekistan. The purpose of the article is to analyze economic growth and its indicators, as well as to develop recommendations for achieving sustainable high rates of economic growth. The author focuses on GDP per capita and concludes that the low level of labor productivity growth in the regions is the result of cheap labor and low skills of workers in the real sector, as well as the existing high level of obsolescence of production capacity.